2013
DOI: 10.1111/bph.12257
|View full text |Cite
|
Sign up to set email alerts
|

A single‐point mutation (Ala280Val) in the third intracellular loop alters the signalling properties of the human histamine H3 receptor stably expressed in CHO‐K1 cells

Abstract: BACKGROUND AND PURPOSEAn alanine to valine exchange at amino acid position 280 (A280V) in the third intracellular loop of the human histamine H3 receptor was first identified in a patient suffering from Shy-Drager syndrome and later reported as a risk factor for migraine. Here, we have compared the pharmacological and signalling properties of wild-type (hH3RWT) and A280V mutant (hH3RA280V) receptors stably expressed in CHO-K1 cells. EXPERIMENTAL APPROACHThe hH3RA280V cDNA was created by overlapping extension P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…The rat H 3 R 413 and H 3 R 397 isoforms that lack 32 and 48 aa in ICL3 showed similar efficacy and higher agonist potency for inhibition of forskolin-induced cAMP formation, but for 42/44mitogen-activated protein kinase (MAPK) phosphorylation, the H 3 R 445 coupled considerably better (Drutel et al, 2001). The naturally occurring A280V mutation on ICL3 also modifies the functionality of the hH 3 R 445 to inhibit cAMP accumulation and stimulate 42/44-MAPK phosphorylation (Flores-Clemente et al, 2013).…”
Section: Determinants Of G Protein-coupling and Activationmentioning
confidence: 99%
“…The rat H 3 R 413 and H 3 R 397 isoforms that lack 32 and 48 aa in ICL3 showed similar efficacy and higher agonist potency for inhibition of forskolin-induced cAMP formation, but for 42/44mitogen-activated protein kinase (MAPK) phosphorylation, the H 3 R 445 coupled considerably better (Drutel et al, 2001). The naturally occurring A280V mutation on ICL3 also modifies the functionality of the hH 3 R 445 to inhibit cAMP accumulation and stimulate 42/44-MAPK phosphorylation (Flores-Clemente et al, 2013).…”
Section: Determinants Of G Protein-coupling and Activationmentioning
confidence: 99%
“…; Flores‐Clemente et al . ). In contrast, other studies give evidence to show that upon activation by an agonist, the H3R exhibits an inhibitory effect on ERK1/2 activation via the activation of PKCα in Mz‐ChA‐1 cells (Francis et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Flores‐Clemente et al . ). However, the underlying molecular mechanisms regulating the H3R‐mediated ERK1/2 activation remain largely unknown (Bongers et al .…”
mentioning
confidence: 97%
“…Several isoforms that might have different pharmacological profiles exists, and there is evidence for genetic polymorphism within the human H 3 R. One, where the amino acid 280 (alanine) is substituted to valine, the H 3 R A280V variant, has been considered a risk factor for migraine . The authors of the study suggested that increase histamine release due to increased population of inactive autoreceptors may be the cause, and in a recent study it was shown that the A280V variant actually reduces the signaling efficacy of the H 3 R …”
Section: The Histamine Dynamics Receptors and Antihistamines In Migmentioning
confidence: 99%
“…114 The authors of the study suggested that increase histamine release due to increased population of inactive autoreceptors may be the cause, and in a recent study it was shown that the A280V variant actually reduces the signaling efficacy of the H3R. 115 By modifying a side chain of the histamine imidazole molecule, selective and potent receptor agonists have been made, so-called (R)-α-methylhistamine compounds (RAMHs). N α -methylhistamine is a histamine catabolite and an H3R agonist that is about 3 times more active than histamine.…”
Section: H1mentioning
confidence: 99%